The Disparity In Judicial Decisions Related To Fraud And Embezzlement Committed By Notaries And/Or Land Deed Officials - Zaki Mahfuz Ridha; Amelia Srikusumadewi; Faizin Sulistio (The Islamic Education and Multiculturalism Foundation, 2024)
Abstract Observing various criminal acts, the law is crucial in addressing criminal issues. Recently, several cases of fraud and embezzlement committed by some Notaries or Land Deed Officials have been frequently encountered. Each of these actions has resulted in different (disparate) criminal sentences due to the judges' legal reasons (Ratio Decidendi). This research uses a normative juridical methodology to align the judges' decisions with the Criminal Code. This study aims to determine the ratio determined by judges and the factors causing the disparity in the imposition of criminal sentences for fraud and embezzlement committed by notaries and/or land deed officials. Additionally, seeking justice in these decisions can create a deterrent effect for Notaries and/or Land Deed Officials who commit fraud and embezzlement. Keywords: Ratio Decidendi; Disparity; Criminal; Notary; Land Deed Official.